Noninvasive 40-Hz Light Flicker Rescues Circadian Behavior and Abnormal Lipid Metabolism Induced by Acute Ethanol Exposure via Improving SIRT1 and the Circadian Clock in the Liver-Brain Axis - Yao, Youli; Zhang, Wenjiang; Ming, Ruibo; Deng, Qiyu; Zuo, Along; Zhang, Shengli; Ying, Ying; Zhao, Yingying; Ma, Junxian (Frontiers in Pharmacology, 2020)
Sirtuin 1 (SIRT1) is a protein deacetylase with important cellular functions, as it regulates numerous processes, including the circadian rhythm in peripheral tissues. Efforts are ongoing to reveal how Sirt1 can be used to treat diseases, such as alcoholic liver disease (ALD), Alzheimer's disease, and liver fibrosis. We have recently shown that non-invasive exposure to 40-Hz light flicker activates hypothalamic SIRT1 gene expression, thereby regulating the central circadian clock. This study investigated the effects of 40-Hz light flicker in a mouse model of ALD. RNA sequencing (RNA-seq) analysis was performed to explore the potential pathways affected by 40-Hz light flicker. We found that 40-Hz light flicker significantly decreased the acute ethanol-induced increases in serum alanine aminotransferase (ALT) and serum triglyceride (TG) levels, and reduced fat-droplet accumulation in mouse livers. Additionally, 40-Hz light flicker significantly suppressed ethanol-induced increases in sterol regulatory element binding protein 1 (SREBP-1) and fatty acid synthase (Fasn) levels. Furthermore, the ethanol induced significant decreases in both Sirt1 levels and phosphorylation of adenosine monophosphate-activated protein kinase (AMPK), compared with those in the control group. Strikingly, pretreatment with 40-Hz light flicker ameliorated such ethanol-induced decreases in SIRT1 levels and AMPK phosphorylation. In addition, ethanol-induced increases in levels of brain and muscle arnt-like protein-1 (BMAL1), circadian locomotor output cycles kaput (CLOCK), and period 2 (PER2) were reversed by 40-Hz light flicker. RNA-seq analysis revealed significant differences in expression of genes related to the AMPK signalling. Moreover, ethanol consumption altered mRNA levels of Sirt1 and circadian genes in the suprachiasmatic nucleus (SCN), indicating that ethanol influenced central pacemaker genes; however, 40-Hz light flicker reversed these ethanol-induced changes. Taken together, our findings demonstrate that 40-Hz light flicker rapidly influence the SCN and exhibits inhibitory properties on hepatic lipogenesis, indicating that 40-Hz light flicker has therapeutic potential for preventing alcoholic liver steatosis.